Pengaruh Strategi STP (Segmenting, Targeting, Positioning) Terhadap Keputusan Pembelian - Tumini Tumini; Joni Hendra; Sentris Ranjanis (Ecobuss, 2021)
This research was conducted in the District of Kanigaran, Probolinggo City with the aim to determine the effect of Segmenting, Targetting, Posisioning (STP) on the purchase decision of automatic motorcycles in the District of Kanigaran, Probolinggo, both simultaneously and partially, and to find out which variable between segmentation, targeting and positioning had the dominant influence on decision to buy an automatic motorcycle.This type of research is quantitative research with causal associative relationships. The variables used consist of independent variables namely STP and the dependent variable is the purchase decision. The sample used was 97 respondents. Data analysis methods used are validity test, reliability test, classic assumption test, multiple regression analysis, F test, t test and dominant.The results of this study indicate that segmentation, targeting and positioning have a significant effect on purchasing decisions of automatic motorbikes.,with the results of the hypothesis testing simultaneously which proves that there is a significant simultaneous effect between on the purchase decision of automatic motorcycles in KanigaranSubdistrict, Probolinggo City. Keywords: Segmenting, Targeting, Positioning, Buying Decision